Determination of Work Motivation, Leadership Style, Employee Competence on Job Satisfaction and Employee Performance - Hajiali, Ismail; Fara Kessi, Andi Muhammad; Budiandriani, B.; Prihatin, Etik; Sufri, Muhammad Mukhlis (Golden Ratio of Human Resource Management, 2022)
The goal of this study was to look at the impact of work motivation, leadership style, and competence on job satisfaction, as well as the effects of work motivation, leadership style, and competence on performance, job satisfaction's impact on performance, and the impact of work motivation, leadership style, and competence on performance via job satisfaction. The research will take place at LLDIKTI-IX. The study's population and sample size were 125 employees (complete sampling). The data from the questionnaire was analyzed with the use of AMOS 18 and the Structural Equation Model. According to the findings, work motivation has a negative and significant impact on job satisfaction. Employee motivation in existence, connectedness, and growth is still low, but it is necessary to improve employee job satisfaction. Employee performance is influenced by competence in a positive but insignificant way. Employee competency is still a career development issue, with little attention paid to the role of innovation and technology in improving employee performance. Employee performance is influenced by competence through job satisfaction in a positive but insignificant way. Employee job satisfaction is poor in enhancing their performance since applying competencies that have been directed thus far is still like meeting work needs.